Achieving advantages from business-to-business electronic commerce: an empirical validation of an integrative framework. (11th November 2008) - N'Da, Koffi; Bergeron, Francois; Raymond, Louis
This study aims at contributing to a better understanding of business-to-business Electronic Commerce (EC) advantages and determinants of these advantages. A research model was empirically tested on a sample of 143 Canadian companies. Key findings indicate that the most important advantages of EC are increased productivity, increased quality of products and services, competitive advantage, and to a lesser extent, sales growth and increased revenues. Cost reductions were marginal. The main determinants of EC advantages include the type of EC use, and the internal and external integrations of EC applications. The strategic orientation of the firm and the organisational context exert only an indirect effect on EC advantages.